Morphology and physiology of lamina I neurons of the caudal part of the trigeminal nucleus - Sedláček, Miloslav; Horák, Martin; Vyklický, Ladislav (Neuroscience, 2007)
It has been suggested that in mammals, trigeminal lamina I neurons play a role in the processing and transmission of sensory information from the orofacial region. We investigated the physiological and morphological properties of trigeminal subnucleus caudalis (Sp5C) lamina I neurons in slices prepared from the medulla oblongata of 13- to 15-day-old postnatal rats using patch-clamp recordings and subsequent biocytin-streptavidin-Alexa labeling. Twenty-five neurons were recorded and immunohistochemically stained. The Sp5C lamina I consisted of several types of neurons which, on the basis of their responses to somatic current injection, can be classified into four groups: tonic neurons, which fired throughout the depolarizing pulse; phasic neurons, which expressed an initial burst of action potentials; delayed onset neurons, which showed a significant delay of the first action potential; and single spike neurons, characterized by only one to five action potentials at the very beginning of the depolarizing pulse even at high levels of stimulation intensity. Electrical stimulation of the spinal trigeminal tract evoked AMPA receptor-mediated excitatory postsynaptic currents (EPSC) exhibiting a strong polysynaptic component. AMPA receptor-mediated miniature excitatory postsynaptic currents (mEPSC) were characterized by a 10-90% rise time of 0.50+/-0.06 ms and a decay time constant of 2.5+/-0.5 ms. The kinetic properties of NMDA receptor-mediated EPSCs were measured at +40 mV. The 10-90% rise time was 8+/-2 ms and the deactivation time constants were 94+/-31 and 339+/-72 ms, respectively. Intracellular staining and morphological analysis revealed three groups of neurons: fusiform, pyramidal, and multipolar. Statistical analysis indicated that the electrophysiological properties and morphological characteristics are correlated. Tonic and phasic neurons were fusiform or pyramidal and delayed onset and single spike neurons were multipolar. Our results show that both the physiological and morphological properties of Sp5C lamina I neurons exhibit significant differences, indicating their specific integration in the processing and transmission of sensory information from the orofacial region.
Keywords: financování organizované; Animals; membránové potenciály; Rats, Wistar; Electrophysiology; synapse; Immunohistochemistry; pyramidové buňky; Membrane Potentials; Pyramidal Cells; Excitatory Postsynaptic Potentials; Receptors, AMPA; Algorithms; imunohistochemie; Trigeminal Nuclei; Financing, Organized; Data Interpretation, Statistical; Receptors, N-Methyl-D-Aspartate; polarita buněk; interpretace statistických dat; Patch-Clamp Techniques; AMPA receptory; excitační postsynaptické potenciály; Cell Polarity; algoritmy; krysa rodu Rattus; elektrofyziologie; receptory N-methyl-D-aspartátu; nuclei trigemini; zvířata; metoda terčíkového zámku; Synapses; Rats; potkani Wistar